Thinking, a diverse and inclusive process: An epistemological look - Tome, Jose Manuel Salum (Seven Editora, 2023)
Contemporary education has taken on the challenge of promoting different programs aimed at promoting inclusive teaching-learning processes that facilitate attention to diversity. It is evident that the integration of students with special needs in regular educational centers has caused significant changes in the curriculum, infrastructure and training among teachers. In the last ten years, educational inclusion has made significant progress, but much remains to be done to expand inclusive spaces. DOI:https://doi.org/10.56238/sevened2023.006-046